Modifications in the optical and thermal properties of a CR-39 polymeric detector induced by high doses of γ-radiation. (April 2018) - Saad, A.F.; Ibraheim, Mona H.; Nwara, Aya M.; Kandil, S.A.
Abstract: Effects of γ-radiation on the optical and thermal properties of a poly allyl diglycol carbonate (PADC), a form of CR-39, polymer have been investigated. CR-39 detectors were exposed to γ-rays at very high doses ranging from 5.0 × 10 5 to 3.0 × 10 6  Gy. The induced changes were analyzed using ultraviolet-visible spectroscopy (UV–VIS) in absorbance mode, and thermogravimetric analysis (TGA). The UV–visible spectra of the virgin and γ-irradiated CR-39 polymer detectors displayed a significant decreasing trend in their optical energy band gaps for indirect transitions, whereas for the direct ones showed a little change. This drop in the energy band gap with increasing dose is discussed on the basis of the gamma irradiation induced modifications in the CR-39 polymeric detector. The TGA thermograms show that the weight loss rate increased with increase in dose, which may be due to the disordered system via scission followed by crosslinking in the irradiated polymer detector. The TGA thermograms also indicated that the CR-39 detector decomposed in three/four stages for the virgin and irradiated samples. The activation energy for thermal decomposition was determined using a type of Arrhenius equation based on the TGA experimental results. These experimental results so obtained can be well used in radiation dosimetry. Highlights: γ-ray irradiation has been proposed to study CR-39 based NTDs. The effect of wide range of high doses on CR-39 detectors was investigated. Optical and thermal properties of virgin and irradiated CR-39 detectors were studied. The UV spectral results show that the unknown γ-dose can be rapidly estimated. Effectiveness of different irradiation doses against thermal stability was determined.